Strategies for Innovative Development of Tumor-targeted Theranostic Radiopharmaceuticals - HUANG Xuhu1, 2, 3, CHEN Huan1, 2, 3, LI Kexin1, 2, 3, WANG Ning1, 2, 3, ZHUANG Jin1, 2, 3, LI Hongyu1, 2, 3, DU Jin2, 3, 4 (Yuanzineng kexue jishu)
Radiopharmaceutical is an essential component of nuclear medicine and have demonstrated significant potential in disease diagnosis and treatment. In recent years, several tumor-targeted theranostic radiopharmaceuticals have been approved for market launch, ushering in a new era of targeted radionuclide therapy and theranostics. The global radiopharmaceutical industry is experiencing vigorous growth, and the research and development of tumor-targeted radiopharmaceuticals in China is transitioning from generic drugs to innovative drugs. The innovation of tumor-targeted radiopharmaceuticals is a complex systematic engineering task which requires comprehensive consideration and synergistic optimization of multiple aspects, including target, radionuclide, chelator, linker, and targeting ligand. In this paper, the above five aspects were reviewed to provide insights for the innovative development of radiopharmaceuticals. First, the strategies for selecting target and radionuclide were summarized and the development strategies of chelator for novel radionuclides were analyzed. Subsequently, taking PSMA-targeted radiopharmaceuticals based on small molecules as examples, the development strategies for targeting ligand and linker were discussed. Additionally, the emerging novel technologies and strategies for the development of theranostic radiopharmaceuticals, including radiohybrid strategies, dual-target strategies and covalent strategies were described. Finally, the challenges faced by the innovative development of tumor targeted radiopharmaceuticals were summarized and analyzed, and the future direction was prospected, with the hope of providing reference for the innovative development of radiopharmaceuticals in China.